SUMBANGAN MODEL PEMBELAJARAN KONTEKSTUAL TERHADAP HASIL BELAJAR PADA MATA PELAJARAN GEOGRAFI - Merliyana Merliyana; Pargito Pargito; Dedy Miswar (JPG (Jurnal Penelitian Geografi), 2014)
This research aims to identify the average score of learning output of the student in geography focusing on population dynamics of the second grade of social science class in SMA N 08 Bandar Lampung, academic year 2013/2014. To identify the contribution between the contextual teaching learning towards the learning output in the subject of geography about populations dynamics of the second grade of social science class of SMA N 08 Bandar Lampung academic years 2013/2014. The method applied in this research was quasi experiment method.. The samples of this research were 60 students. The data analysis method used in this research was T test, independent sample T test.The result of data analysis conclude that the use of contextual teaching learning model in giving the significant contribution towards the learning output of citizenship dynamics in geography subject of the students. The learning output of the student by applying the contextual teaching learning is bettter (higher) than the output without applying the contextual teaching learning. Penelitian ini bertujuan untuk mengetahui nilai rata-rata hasil belajar siswa pada mata pelajaran geografi tentang dinamika kependudukan kelas XI IPS di SMA Negeri 08 Bandar Lampung TA: 2013/2014. Untuk mengetahui sumbangan antara pembelajaran kontekstual (contextual teaching learning) terhadap hasil belajar pada mata pelajaran geografi tentang dinamika kependudukan kelas XI IPS di SMA Negeri 08 Bandar Lampung TA: 2013/2014. Metode yang digunakan pada penelitian ini adalah  metode eksperimen semu. Jumlah sampel sebanyak 60 siswa. Analisis data yang digunakan adalah  uji t independent samples t test. Hasil analisis data diperoleh kesimpulan bahwa: Penggunaan model pembelajaran berbasis kontekstual memberikan sumbangan yang signifikan terhadap hasil belajar dinamika kependudukan oleh siswa. Hasil belajar siswa dengan model pembelajaran berbasis kontekstual lebih tinggi dibandingkan dengan tanpa model pembelajaran berbasis kontekstual.Kata kunci: hasil belajar, model, pembelajaran kontekstual